R graphics - Murrell, Paul (The R series, 2019)
"This is the third edition of a very successful book on using R for graphics by one of the leaders in the field. This is a major update, with a complete overhaul in focus and scope. It will now focus primarily on the two core graphics packages in R - graphics and grid - and has a new section on integrating graphics. This section includes two new chapters on combining graphics systems and web graphics. The section on other graphics packages has been removed, with discussion of some of these packages integrated with other parts of the book, where appropriate. The book will remain the key reference for the core graphics systems in R"--